Angiotensin I-Converting enzyme (ACE) inhibitory and dipeptidyl Peptidase-4 (DPP-Ⅳ) inhibitory activity of umami peptides from Ruditapes philippinarum. (June 2021) - Zhang, Yue; Pan, Daodong; Yang, Zhengcang; Gao, Xinchang; Dang, Yali
Abstract: The functional activity of umami peptides after digestion is poorly known. We studied the dipeptidyl peptidase-4 (DPP- IV) and angiotensin I-converting enzyme (ACE) inhibition activity of 14 umami peptides from Ruditapes philippinarum in vivo and in vitro . GRVSNCAA (IC50 = 57.93 μmol/L) and TYLPVH (IC50 = 1.37 μmol/L) exhibited noncompetitive ACE inhibitory activity in vitro, and GPAGPAGPR showed DPP-IV inhibitory activity (IC50 = 160.5 μmol/L). The peptides also decreased systolic blood pressure and reduced the blood sugar level in the oral glucose tolerance test and the single blood pressure test. To understand the hypoglycemic and hypotensive mechanism of peptides, we conducted cell experiments with HepG2 and human umbilical vein endothelial cells. GRVSNCAA and TYLPVH significantly (p < 0.01) promoted nitric oxide secretion and reduced endothelin-1 production. GPAGPAGPR exerted hypoglycemic activity by increasing the content of hexokinase and pyruvate kinase.These results suggest that some umami peptides have the potential to provide human health benefits. Highlights: The functional activity of 14 umami peptides after digestion was studied. Umami peptide GRVSNCAA and TYLPVH had ACE inhibitory activity in vitro and in vivo . Umami peptide GPAGPAGPR showed DPP-Ⅳ inhibitory activity in vitro and in vivo .